Epidemiology and Risk Factor Analysis of Children with Bronchiolitis Admitted to the Intensive Care Unit at a Tertiary Care Center in Saudi Arabia - Sara Osman; Abdulqader Alaa adeen; Omar Hetta; Abdulaziz Alsiraihi; Mahmoud Bader; Alwaleed Aloufi; Amir Abushouk; Mohammed Yasir Al-hindi (MDPI AG, 2023)
Bronchiolitis is a leading cause of hospitalization worldwide for children aged ≤2 years. Few studies have compared general ward and pediatric intensive care unit (PICU) admissions, particularly in Saudi Arabia. This retrospective cohort study aimed to compare the demographic and clinical characteristics of children with bronchiolitis admitted to the general ward with those admitted to the PICU. Children (≤6 years) previously diagnosed with bronchiolitis and admitted to the PICU or general ward at a tertiary center in Saudi Arabia between May 2016 and May 2021 were included. Multiplex polymerase chain reaction was used to identify respiratory viruses. Of the 417 patients enrolled, 67 (16.06%) were admitted to the PICU. The PICU group was younger (median, 2 months; interquartile range [IQR], 1-5 months) vs. (6 months; IQR, 2.65-13.25 months). There was a dramatic reduction in bronchiolitis admissions during the COVID-19 pandemic. The most common causative virus was respiratory syncytial virus (RSV) (54.9%). In the multivariate regression analysis, hypoxia, hyperinflation on X-ray, and non-RSV bronchiolitis were independently associated with PICU admission. However, a higher chronological age and cough were protective. Children with Down syndrome, immunodeficiency, or neuromuscular disorders, and intermediate preterm infants (29-33 weeks of gestation) are at a high risk of PICU admission (adjusted odds ratio: 2.4, 7.1, 2.9, and 2.9; p = 0.037, 0.046, 0.033, and 0.029, respectively). Bronchiolitis is still one of the leading causes of PICU admission. Particular attention should be paid to preventive measures, especially in the post-COVID-19 era, targeting high-risk groups.